IN VITRO AND IN VIVO ANTIMALARIAL ACTIVITY OF DCM EXTRACT OF AGATHOSMA BETULINA - Sekhoacha, M.; Campbell, W.; Smith, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The problem of drug resistance of Plasmodium species has emphasised the need for more effective alternative treatment for malaria. The study investigates the antimalarial potential of a South African medicinal plant, Agathosma betulina. The aerial parts of A. betulina were obtained from Grassroots Cape Botanicals in Stellenbosch. The in vitro antiplasmodial activity was assessed in a bioassay of cultured blood stage parasites of P. falciparum using the pLDH assay. Cytotoxicity was tested on CHO mammalian cell line using MTT assay. The in vivo antimalarial activity was investigated in Plasmodium ANKA mouse model. The DCM extract was fractionated using Solid Phase Extraction and HPLC. Active compounds were identified by GC-MS. The DCM extract showed in vitro antiplasmodial activity (IC50 = 14.4 µgml-1) and low cytotoxicity (IC50 = 170 µgml-1). Three fractions showed enhanced in vitro antiplasmodial activity with IC50 values in the range of 1.6-2.8 µgml-1, and low cytotoxicity (IC50 > 100 µgml-1). These fractions combined showed no toxicity effects in vivo when administered at 500mg/kg daily for 7 consecutive days, and showed good antimalarial activity when given at 250mg/kg daily for 4 days. The fractions exhibited parasite inhibitory activity and good prophylactic effect with parasitaemia suppression averages of 60% and 75% respectively. The active components were identified as hepatodenoic acid, hexadenoic acid, phosphoric acid, and 9,-12-octanedenoic acid.